2010
DOI: 10.1111/j.1365-2702.2009.02997.x
|View full text |Cite
|
Sign up to set email alerts
|

An Australian investigation of emotional work, emotional well‐being and professional practice: an emancipatory inquiry

Abstract: As the demand for community palliative care increases, the issues that limit and enhance the emotional well-being of generalist palliative care nurses' become critical. The findings have international relevance to generalist and specialist palliative care nurses, academics and researchers alike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 55 publications
3
54
0
Order By: Relevance
“…Work‐related well‐being is a key factor in determining an organization’s long‐term performance. Experiencing emotional well‐being can enhance nurses’ ability to manage the demands associated with the quality of patient care (Rose & Glass 2010). In addition, a great number of studies have identified nurses’ well‐being such as low job satisfaction and burnout as causes of nursing personnel turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Work‐related well‐being is a key factor in determining an organization’s long‐term performance. Experiencing emotional well‐being can enhance nurses’ ability to manage the demands associated with the quality of patient care (Rose & Glass 2010). In addition, a great number of studies have identified nurses’ well‐being such as low job satisfaction and burnout as causes of nursing personnel turnover.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more continuous rather than more intermittent demands can make the health care professional more vulnerable to BS. 35,36 Professional practice is considered to be a predominantly emotional activity, 37 i.e., it depends on the worker's stability and ability to deal with emotions. In the process model proposed for BS, when such attempts fail, the worker starts to adopt distant attitudes towards their patients in an attempt to reduce the perception of emotional exhaustion resulting from interactions often characterized by negative emotions on both parts.…”
mentioning
confidence: 99%
“…The use of adaptive or coping strategies like Seeking support and finding solutions was also important to our participants. Another study on palliative care nurses exploring the relationship between emotional well-being and professional practice described the significance of having a sense of balance or equilibrium, 33 which support from colleagues, friends, and family can provide.…”
Section: Main Findingsmentioning
confidence: 99%